PENYULUHAN TENTANG PENGGUNAAN MODEL PEMBELAJARAN THINK TALK WRITE PADA SISWA KELAS X SMK YAPIM BIRU – BIRU - Mona Fitri Gurusinga; Afrilius Simanjuntak (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
This counseling purpose to know use of the Think Talk Write (TTW) Learning Model on Students' Ability to Write Persuasion Texts by Class X Students of SMK YaPIM Biru - Biru which consists of 7 classes with a total population of 240 students. From the determined population, 64 students were determined with a total of two classes selected by cluster sampling, namely class X 3 and class X 4. The data information technique used was normality test using the F test, homogeneity test and hypothesis testing using the "t" test. The results of the research, concluded that the Talk Think Write (TTW) Study Model can improve student learning outcomes in writing persuasion texts.